A review of the Tychobythinus algiricus species group from North Africa (Coleoptera: Staphylinidae: Pselaphinae) - Sabella, Giorgio; Viglianisi, Fabio Massimo; D’urso, Vera; Nouira, Said (Zootaxa, 2014)
The species belonging to the Tychobythinus algiricus group are revised and the group is characterized and defined. Tychobythinus algiricus (Raffray, 1871) is redescribed, illustrated and its distribution and its synonymic framework discussed, establishing that Tychobythinus occidentalis Besuchet, 1962 is a junior synonym of Tychobythinus algiricus (syn. nov.). A key for species identification is provided.